An overview of the Bantoid languages - Roger Blench (Afrika und Übersee)
The Bantoid languages are a body of some 150-200 languages positioned geographically between Nigeria and Cameroun. They do not form a genetic group, but all are in some way related to Bantu more closely than other branches of Benue-Congo. The most well-known branches are Dakoid, Mambiloid, Tivoid, Beboid, Grassfields, and Ekoid. Bendi, formerly Cross River, may be Bantoid, while Jarawan is probably Narrow Bantu. Their classification is controversial. Due to their inaccessibility, many are poorly described. The article summarises the literature on their classification and main linguistic features, and in particular how these relate to Bantu. It also includes a brief survey of endangerment of smaller languages and the state of literacy development. Their main typological characteristics include S (AUX) OV word order, functioning or fossilised nominal affixing and concord (sometimes alliterative), suffixed verbal extensions, ATR vowel harmony and labial-velars in the phonology. Some languages have developed highly complex tone-systems as a result of extreme erosion of segmental material.